2015
DOI: 10.1007/s00344-015-9534-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Plant Growth-Promoting Rhizobacteria on Maize Growth and Cadmium Uptake

Abstract: Maize is a plant known for food, feed, and energy value, but being a greater biomass, it may also be utilized to extract pollutants from soil. Plant growth-promoting rhizobacteria (PGPR) may act as biofertilizer to improve plant health and indirectly may enhance metal extraction. This study focuses on five bacterial strains isolated from the vegetable (Bitter gourd) rhizosphere irrigated with industrial effluent and characterized for various plant growth-promoting activities. Based on 16S rRNA gene sequencing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(56 citation statements)
references
References 39 publications
(7 reference statements)
8
46
0
2
Order By: Relevance
“…It is reported that PGPR improves the stomatal aperture to uptake more water via roots and enhances the stomatal conductance as compared to non-PGPR inoculated plants (Vejan et al 2016). (Ahmad et al 2016) described that PGPR enhanced the water uptake, RWC and membrane stability in the leaf of maize plant under Cd stress which support our study. Moreover, PGPR efficiently improved the tolerance ability of plants exposed to various environmental stresses including heavy metals and increased the yield of plant (Enebe and Babalola 2018).…”
Section: Discussionsupporting
confidence: 87%
“…It is reported that PGPR improves the stomatal aperture to uptake more water via roots and enhances the stomatal conductance as compared to non-PGPR inoculated plants (Vejan et al 2016). (Ahmad et al 2016) described that PGPR enhanced the water uptake, RWC and membrane stability in the leaf of maize plant under Cd stress which support our study. Moreover, PGPR efficiently improved the tolerance ability of plants exposed to various environmental stresses including heavy metals and increased the yield of plant (Enebe and Babalola 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Soil microbial activity is known to increase Cd availability via excretion of organic acids and subsequent solubilization of Cd-bearing minerals Liu et al 2014a, b;Ahmad et al 2015). Soil amendment with Cd-solubilizing microorganisms such as plant growth-promoting bacteria (PGPR) is a very effective technique for enhancing Cd bioavailability (Belimov et al 2005).…”
Section: Influence Of Soil Microbial Activity On CD Behavior In Soilmentioning
confidence: 99%
“…The type of exposure (shoot or root) may have different effects on metal compartmentalization (distribution at the tissue and cellular scale) in plants [143,253] and consequently metal bioavailability and toxicity. In case of heavy metal uptake by plant roots, the major portion of absorbed metals especially Pb (about 95% or even more) is sequestered in the root cells, with a limited translocation to aerial tissues unless the plant is chelates-assisted or hyperaccumulator [209,254,255] or microbial assisted [256]. The restricted translocation of heavy metals to aerial plant tissues is due to the presence of physical barrier (Casparian strip) in plant roots [36], precipitation intercellular space as insoluble metal-salts [257], or sequestration in the vacuoles of cortical or rhizodermal cells [258].…”
Section: Comparison Of Heavy Metal Compartmentalization After Foliar mentioning
confidence: 99%
“…The variation in metal speciation under foliar and root uptake can be due to variation in rhizosphere and/or the phyllosphere zones as well as mode transportation of metals inside plants [263,264]. The rhizosphere hosts an intense microbial activity and is a place of excretion of various inorganic and organic compounds [256,[265][266][267]. Thus, these mechanisms involved in the rhizosphere and/or the phyllosphere zones could be effectively responsible for the observed metal speciation and compartmentalization changes as a function of the plant species (as, for instance, the nature and quantities of root and foliar exudates depend on the plant considered).…”
Section: Comparison Of Heavy Metal Speciation After Foliar and Root Pmentioning
confidence: 99%